1996
DOI: 10.1002/(sici)1097-4652(199603)166:3<495::aid-jcp4>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous leukocyte and endogenous elastases can mediate mitogenic activity in pulmonary artery smooth muscle cells by release of extracellular matrix-bound basic fibroblast growth factor

Abstract: There is increasing evidence that extracellular matrix (ECM)-degrading proteinases contribute to the process of medial hypertrophy and neointimal proliferation in pulmonary vascular diseases. However, little is known about how proteinases, specifically elastases, induce vascular smooth muscle cell (SMC) hyperplasia. Our objective was to determine whether exogenous human leukocyte elastase (HLE), as well as endogenous vascular elastase, could release basic fibroblast growth factor (bFGF), a potent mitogen store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(94 citation statements)
references
References 48 publications
4
90
0
Order By: Relevance
“…Fragmentation of elastic laminae generates elastin peptides and releases growth factors from the extracellular matrix, and these molecules can induce proliferation and migration of SMC. 16 Indeed, we observed a significant increase in the number of proliferating SMC in the neointimal lesions of PAs in S100A4 versus C57 mice 6 months after M1-MHV-68 infection, as judged by positivity for proliferating cell nuclear antigen (PCNA) (P Ͻ 0.05; Figure 2, C and D). Interestingly, formation of these neointimal lesions was not sufficient to elevate the right ventricular systolic pressure or to cause right ventricular hypertrophy (see Supplemental Figure S2 at http://ajp.amjpathol.org), a finding also observed in other models with neointimal lesions.…”
Section: Fragmentation Of Pa Elastin In S100a4 Mice Is Associated Witmentioning
confidence: 84%
See 3 more Smart Citations
“…Fragmentation of elastic laminae generates elastin peptides and releases growth factors from the extracellular matrix, and these molecules can induce proliferation and migration of SMC. 16 Indeed, we observed a significant increase in the number of proliferating SMC in the neointimal lesions of PAs in S100A4 versus C57 mice 6 months after M1-MHV-68 infection, as judged by positivity for proliferating cell nuclear antigen (PCNA) (P Ͻ 0.05; Figure 2, C and D). Interestingly, formation of these neointimal lesions was not sufficient to elevate the right ventricular systolic pressure or to cause right ventricular hypertrophy (see Supplemental Figure S2 at http://ajp.amjpathol.org), a finding also observed in other models with neointimal lesions.…”
Section: Fragmentation Of Pa Elastin In S100a4 Mice Is Associated Witmentioning
confidence: 84%
“…We identified the elastase involved as neutrophil elastase (NE) produced by PA SMC, suggesting that it is the endogenous vascular elastase previously related to PAH in other experimental models. 12,16,18,19 Moreover, we showed that NE is produced in significantly greater amounts by cultured murine S100A4 versus C57 PA SMC, and by human PA SMC from IPAH versus control lungs, and we localized NE to neointimal and plexiform lesions in human lung specimens.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…It is possible that these cytokines initiate a cascade of events leading to VSMC proliferation that is later amplified by the release of vasoactive mediators and growth factors that alter vessel wall structure and function. For example, the initial injury and loss of endothelial barrier function can lead to extravasation of serum and activation of endogenous elastolytic activity from vascular smooth muscle cells (27,28). Increased serine elastase activity results in proteolytic degradation of extracellular matrix and the release of matrix-bound growth factors amplifying smooth muscle cell proliferation and remodeling of the pulmonary arterioles (27,29).…”
Section: Discussionmentioning
confidence: 99%